The renegades : a novel - Parker, T. Jefferson (Parker, T. Jefferson. Charlie Hood novel., 2009)
Sheriff's deputy Charlie Hood is transferred to the supposedly quiet desert community of Antelope Valley, only the quietness is shattered one night during a routine call: someone guns down his partner, Terry Laws, in their patrol car. Hood is out to find the killer Wild West style.